Risk of neutropenia associated with Sacituzumab govitecan: a systematic review combined with the FAERS database and meta-analysis - Xu, Yin-Xue; Shen, Qian; Lu, Xiu-Fen; Shen, Xiao-Lan; Zhang, Lei; Qiao, Xi-Wen; Zhang, Xue-Hui (Frontiers in Pharmacology, 2026)
ObjectiveSacituzumab govitecan (SG) has emerged as a therapeutic option for various cancers. Increasing reports of SG-associated neutropenia have attracted attention, emphasizing the need to fully characterize this risk.MethodsThis study conducted a retrospective pharmacovigilance analysis using the Food and Drug Adverse Event Reporting System (FAERS) database. Cases of neutropenia associated with SG were extracted from the second quarter of 2020 through the second quarter of 2025 for disproportionality analysis. Additionally, a meta-analysis was performed on randomized controlled trials (RCTs) comparing SG (experimental group) with chemotherapy drugs (control group), retrieved from CNKI, Wanfang, VIP, PubMed, the Cochrane Library, EMBASE, and Web of Science.ResultsIn the FAERS, 500 cases of neutropenia were associated with SG treatment. Among antibody-drug conjugate (ADC) drugs, SG exhibited the strongest positive signal (reported odds ratio (ROR) = 17.91, 95% CI: 16.39–19.56). Subgroup analysis revealed that this signal widely existed in different gender, age, reporting groups and initial indications. Most events occurred within 30 days of initial initiation. Gender (10 days for males vs. 13 days for females, P < 0.05) and initial indications (12 days for breast cancer/lung cancer vs. 8 days for bladder cancer, P < 0.05) were significantly associated with time-to-onset. Five RCTs were included in this meta-analysis. The results showed that for all adverse event (AE) grades, SG is associated with an increased risk of neutropenia (odds ratio (OR) = 2.07, 95% CI: 1.09–3.93, P < 0.05). Subgroup analysis indicated that SG significantly increased the risk of all-grade neutropenia AE in patients with breast cancer (OR = 2.13, 95% CI: 1.68–2.69, P < 0.00001), and a similar trend was observed among bladder cancer patients (P < 0.00001). Although no significant difference emerged in the risk of all-grade AEs for lung cancer patients (P > 0.05), the control group exhibited a tendency toward higher risk, and the SG group demonstrated a significantly lower incidence of grade ≥3 AEs compared to controls (P < 0.05). In addition, the risk of neutropenia did not differ significantly between patients with the UGT1A1*1/*28 and UGT1A1*28/*28 genotypes compared to those with the UGT1A1*1/*1 genotype (P > 0.05).ConclusionThe combined analysis supports an elevated risk of neutropenia associated with SG. This AE exhibits significant cancer species specificity. Early intervention and management of neutropenia are therefore of considerable clinical importance.